A Kantian Critique of Grotius - Marey, Macarena (Problemos, 2019)
[full article, abstract in English; abstract in Lithuanian]During the last few years, it has become usual to turn to some seventeenth century readings of the traditional idea of an original common possession of the earth for philosophical aid to explain and support the rights of persons in situations of extreme need, including refugees. Hugo Grotius’s conception of this idea is one of the most cited ones. In this paper, I hold that a Grotian reading of the idea of an original common possession of the earth is not a fruitful principle if we want to elaborate a solid defence of the rights of the ones in need. I reconstruct and analyse the role this idea has in Grotius’s theory of private property and present objections to it from a Kantian perspective.
Keywords: original common possession; property rights; Grotius; Kant